Process-Genre Approach, Product Approach, and Students’ Self-Esteem in Teaching Writing - M. Ali Ghufron (Indonesian EFL Journal: Journal of ELT, Linguistics, and Literature, 2016)
This research was aimed at revealing whether or not: (1) process-genre approach is more effective than product approach in teaching writing; (2) students who have high self-esteem have better writing skill than those who have low self-esteem; and (3) there is an interaction between teaching-learning approaches and students’ self-esteem in teaching writing. This experimental research involved two classes of third semester students of English Education Study Program of IKIP PGRI Bojonegoro. Each class consisted of 38 students. The writing test and questionnaire on self-esteem were used as the instruments to collect the data of this research. The results show that: (1) Process-Genre Approach is more effective than Product Approach in teaching writing; (2) the students who have high self-esteem have better writing skill than those who have low self-esteem; and (3) there is an interaction between teaching approaches and the students’ self-esteem in teaching writing. Therefore, it is suggested to implement Process-Genre Approach since the students can experience every stage of writing process in order to deliver the message in their writing properly.